Soil suction and shear strength of compacted soil - Phoong, Bo Jun. (2013)
Shear strength of soils is governed by several parameters, including soil fabric and suction. The study carried out in this report aims to connect the dots between shear strength and suction by carrying out suction measurement and compression tests on compacted residual soil specimens. Residual soils from a construction site in NTU were used in the project. The residual soils were compacted using two compaction efforts: standard and improvised Proctor. The shear strength of the compacted soil was determined using unconfined compression test and unconsolidated undrained tests at 50 and 100 kPa confining pressure. The suctions of the compacted soil samples were measured using high suction tensiometer and the chilled-mirror dew-point technique. The test results showed that the higher the dry density of the compacted soil, the higher the shear strength of the soil. Suction of the compacted soil samples decreases non-linearly with increasing water content.